ENTRE EL OPTIMISMO Y EL DESENCANTO. LA REFORMA UNIVERSITARIA Y SU RECEPCIÓN EN LA PRENSA DE ENTRE RÍOS (1918–1921) (De Signos y Sentidos, 2018)
The present work tries to give an account of the political and cultural meanings that the University Reform had in the region, in relation to the national and international events of the period. Two periodical publications from the city of Paraná —La Acción and El Diario— are selected to analyze how they represented the development of the movement. The moment analyzed covers the hottest months of the reform, from mid–1918 to the first months of the year 1921. A series of questions will guide our inquiry. The answer to each of them, will try to retrace tensions and contradictions that the scenario inaugurated by the University Reform aroused among its contemporaries.
Keywords: University Reform; city of Paraná; periodical press; discourse